Water use pattern of Pinus tabulaeformis in the semiarid region of Loess Plateau, China - Jian, Shengqi; Zhang, Xueli; Wu, Zening; Hu, Caihong (Forest Systems, 2016)
Aim of the study: We analyzed the water-use strategy of P. tabulaeformis and determine the relationships between environmental factors and transpiration rates in the P. tabulaeformis woodlands. Area of study: Loess Plateau region of Northwest China. Material and Methods: Sap flow density of the P. tabulaeformis trees was measured with Granier-type sensors. Stand transpiration was extrapolated from the sap flow measurements of individual trees using the following Granier equation. Main results: The mean sap flow rates of individual P. tabulaeformis trees ranged from 9 L day−1 to 54 L day−1. Photosynthetically active radiation and vapor pressure deficit were the dominant driving factors of transpiration when soil water content was sufficient (soil water content>16%), considering that soil water content is the primary factor of influencing transpiration at the driest month of the year. During the entire growing season, the maximum and minimum daily stand transpiration rates were 2.93 and 0.78 mm day−1, respectively. The mean stand transpiration rate was 1.9 mm day−1, and the total stand transpiration from May to September was 294.1 mm. Research highlights: This study can serve as a basis for detailed analyses of the water physiology and growth of P. tabulaeformis plantation trees for the later application of a climate-driven process model. Keywords: Sap flow; stand transpiration; environmental factor; Pinus tabulaeformis; Loess Plateau.